The logic of Germany's China policy in the Zeitenwende - Nadine Godehardt (Stiftung Wissenschaft und Politik (SWP), 2024)
So far, there has been no sign of a Zeitenwende in Germany's China policy. No comprehensive structural changes or adjustments in China-related institutions and administration have been observed (so far). Germany's China policy in recent years has been characterised by the need to safeguard Germany as a business location. Germany's Strategy on China is therefore more of a strategy on Germany. There is no overarching, long-term goal for German-Chinese relations. The logic of Germany's China policy is driven by two principles of action: self-protection and political indifference. Self-protection is more inward-looking ("safeguarding the domestic political system"), political indifference is more outward-looking ("dealing with China"). Both principles are linked by a reactive element. The characterisation of China as a "partner, competitor and systemic rival" is no longer appropriate and must be updated. Germany's China policy needs a debate on goals that should determine German-Chinese relations in the future. As well as a debate on goals, a debate on preparedness will be necessary to permanently relieve the burden on relevant institutions and the administration and prepare them for future challenges in dealing with Chinese actors.
Keywords: 320; Zeitenwende; Germany's China policy; self-protection; political indifference; preparedness; Federal Chancellor Olaf Scholz; de-risking; Xi Jinping; Chinese Communist Party (CCP)